1988
DOI: 10.1177/109634808801200106
|View full text |Cite
|
Sign up to set email alerts
|

Herzberg's Proposals and Their Applicability To the Hotel Industry

Abstract: Two implications of Herzberg's Two-Factor theory were derived and tested empirically, using data obtained from 287 people employed by twenty hotels in Greece. The results supported the hypothesis that when the organization does not allow workers the opportunity to satisfy most of their needs, hygiene factors become powerful sources of motivation, leading to improved performance and thus to productivity. On the other hand, very little contribution to productivity is due to motivators. The findings were interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…It was found that hygiene factors were more common and dominant in the hospitality industry than in other industries, this can be refereed to some employees who are working in the hospitality industry start their jobs with low expectations of being able to satisfy their high needs (Mullins, 1998). Chitiris (1988) confirmed also that employees in the hospitality industry were more concerned with hygiene factors than motivating factors.…”
Section: Job Satisfactionmentioning
confidence: 60%
“…It was found that hygiene factors were more common and dominant in the hospitality industry than in other industries, this can be refereed to some employees who are working in the hospitality industry start their jobs with low expectations of being able to satisfy their high needs (Mullins, 1998). Chitiris (1988) confirmed also that employees in the hospitality industry were more concerned with hygiene factors than motivating factors.…”
Section: Job Satisfactionmentioning
confidence: 60%
“…However, Ukaegbu (2000) explained that for employees working in a depressed economy the extrinsic working conditions are stronger predictors of employee attitudes than intrinsic factors. In addition, Chitiris (1988) posits, when an organization did not allow employees an opportunity to satisfy most of their needs, hygiene factors became more powerful sources of motivation than motivators, and they led to improved performance and productivity. Since the present study was conducted in the depressed state of India with growing unemployment level where meager intrinsic rewards to employees were observed, thereby, substantiate the findings of previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…Despite its provision in providing a general framework for assessing employee behavior in learning, decision making, attitude formation, and motivation (Chen & Lou, 2002as cited in Chiang & Jang, 2008, the theory is criticized of lacking strong theoretical framework and validity of components within the model. Furthermore, a search of the literature indicates that a number of studies on work motivation in the hotel industry have adopted Herzberg's theory (Chitiris, 1988;Lundberg et al, 2009;Sledge, Miles, & Coppage, 2008;Wong, Siu, & Tsang, 1999), as which addresses both intrinsic and extrinsic factors for motivation. Herzberg's two-factor theory bases its idea on the "need theories" and suggests that humans have two different sets of needs and that the factors causing job satisfaction (presumably motivation) are different from those causing job dissatisfaction (Lundberg et al, 2009;Wong et al, 1999).…”
Section: Work Motivation In the Hotel Industrymentioning
confidence: 99%